Global business, local constraints: The case of water in South Africa - Bronwen Morgen (University of Oxford, Global Economic Governance Programme (GEG), 2004)
This paper explores the changing incentives faced by global water companies in light of the political and legal struggle in South Africa over the growing trend of supplying urban drinking water on a commercial, for-profit basis, often by multinational corporations. It traces on the changes in rules and institutions in three spheres - global, national and local - affecting the strategies and behaviour of companies in the water services sector. The case of South Africa is an especially interesting intersection of these three levels due to its relatively high level of state capacity and fiscal autonomy, its formal constitutional commitment to a human right to water, and the historical legacy of powerful politically organised civil society, actually existing extremely low or non-existent social provision for communities of colour, and strong political will to provide universal access to water. The paper argues that at the global level, key actors involved in funding, managing, regulating and consuming water services are constructing a policy of corporate welfarism in water provision, with three facets: fiscal, administrative, and ideological. This intersects with a national-level legislative and regulatory policy approach that uneasily combines what I call "political" and "transactional" frameworks for the provision of water services, frameworks that are in significant tension with each other. Finally, locally-based resistance in the townships and peri-urban areas to the implementation of key aspects of the national framework has important implications for the viability of corporate water welfarism. Global water companies have responded with a strategy I call "soft consumerism", which are likely to only very partially, if at all, alleviate the substantive political conflict regarding larger structural issues underlying the demands for greater political participation by local actors.
Keywords: 330